Identifying competencies of clinical instructors supervising students in community health nursing - Natividad-Tandoc, Christinelli (1999)
This study aimed to identify the essential competencies a clinical instructor should demonstrate in supervising nursing students in the community setting. The essential competencies were identified through the use of a 2-phase Delphi study. Forty-six (46) respondents participated in the first phase. They were asked to list competencies of clinical instructor in community health nursing. A total of five hundred two (502) competency statements were generated, which after sorting resulted to a final list of 120 competencies. The 120 competencies were then categorized into eight (8), namely: community organizer, health care provider, coordinator/collaborator, advocate, researcher, educator, counselor and clinical instructor. In the second phase, forty-two (42) respondents rated the competencies according to their being essential utilizing a five-point Likert scale. A mean rating of 4.5 was arbitrarily set to identify the competency statements to be included in the final list of competencies. Of the 120 competency statements rated by experts, 68 or 56.66 registered a mean rating of 4.5 and above and 52 or 43.33 registered a mean rating of 4.5 and below. In terms of rating by categories, thirty-five (35) or 81.39 of the competencies as clinical instructor /teacher in CHN were considered essential by experts. Twenty-five (25) or 50 of competencies as community organizer were considered essential. Of the 9 competencies as health care provider, 4 or 44.44 were considered essential. The experts also rated as highly essential the competencies as educator and counselor. Respondents did not consider competencies as advocate and researcher essential. Using the Delphi method the CHN competencies considered by expert respondents as essential were identified. These competencies should be considered highly by all stakeholders involved in nursing education like the clinical instructors, nursing school administrators and the nursing professionals as a whole.
Major project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: Community health nursing